Latin America and Russia: evolution of mutual foreign interests - A R Massarova (RUDN Journal of Economics, 2013)
The article analyses the dynamics of the indicators that define current bilateral economic relations, it examines in details structural and regional shifts in bilateral trade between Latin America and Russia. The analysis revealed the major problems of foreign relations and allowed to set out the ways of their decisions through the diversification of Latin American and Russian mutual trade.